Outcome of Surgical Interventions and Deliveries in Patients with Bleeding of Unknown Cause: An Observational Study - Veen, Caroline S. B.; Huisman, Elise J.; Romano, Lorenzo G. R.; Schipaanboord, Celesta W. A.; Cnossen, Marjon H.; de Maat, Moniek P. M.; Leebeek, Frank W. G.; Kruip, Marieke J. H. A. (Thrombosis and Haemostasis, 2021)
Background The most optimal management for patients with bleeding of unknown cause (BUC) is unknown, as limited data are available.Objective Evaluate management and outcome of surgical procedures and deliveries in patients with BUC.Materials and Methods All patients ≥12 years of age, referred to a tertiary center for a bleeding tendency, were included. Bleeding phenotype was assessed and hemostatic laboratory work-up was performed. Patients were diagnosed with BUC or an established bleeding disorder (BD). Data on bleeding and treatment during surgical procedures and delivery following diagnosis were collected.Results Of 380 included patients, 228 (60%) were diagnosed with BUC and 152 (40%) with an established BD. In 14/72 (19%) surgical procedures major bleeding occurred and 14/41 (34%) deliveries were complicated by major postpartum hemorrhage (PPH). More specifically, 29/53 (55%) of the BUC patients who underwent surgery received prophylactic treatment to support hemostasis. Despite these precautions, 4/29 (14%) experienced major bleeding. Of BUC patients not treated prophylactically, bleeding occurred in 6/24 (25%). Of pregnant women with BUC, 2/26 (8%) received prophylactic treatment during delivery, one women with and 11 (46%) women without treatment developed major PPH.Conclusion Bleeding complications are frequent in BUC patients, irrespective of pre- or perioperative hemostatic treatment. We recommend a low-threshold approach toward administration of hemostatic treatment in BUC patients, especially during delivery.
Keywords: hemostasis; bleeding of unknown cause; von Willebrand disease